2020
DOI: 10.21203/rs.3.rs-78483/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Additive Ti3SiC2 Content on Mechanical Properties of B4C–TiB2 Composites Ceramics Sintered by Spark Plasma Sintering

Abstract: B4C-TiB2 composite ceramics with ultra-high fracture toughness were successfully prepared via spark plasma sintering at 1900℃ using B4C and Ti3SiC2 as raw materials. The results show that compared with pure B4C ceramics sintered by SPS, the hardness of B4C-TiB2 composite ceramics is decreased, but the flexural strength and fracture toughness are significantly improved, especially the fracture toughness has been improved by leaps and bounds. When the content of Ti3SiC2 is 30vol.%, the B4C-TiB2 composite ceramic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Further improvement of their mechanical properties to meet the stringent requirements in extreme service environments has attracted great research interest. Increasing density, forming composites, and reinforcing by fibers or whiskers are conventional methods commonly used to improve ceramics' mechanical properties 5–9 . Unlike metal alloys, ceramics with ionic or covalent bonding seldom employ defects of nanotwins or dislocations to enhance mechanical properties due to the high energy for those defects’ formation and movement 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement of their mechanical properties to meet the stringent requirements in extreme service environments has attracted great research interest. Increasing density, forming composites, and reinforcing by fibers or whiskers are conventional methods commonly used to improve ceramics' mechanical properties 5–9 . Unlike metal alloys, ceramics with ionic or covalent bonding seldom employ defects of nanotwins or dislocations to enhance mechanical properties due to the high energy for those defects’ formation and movement 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that adding Si or P to the grain boundaries might improve ductility. Several approaches, such as microalloying, 12–16 stoichiometry control, 17–19 and addition of a second phase, 20–22 have been proposed to mitigate amorphous shear band formation. For microalloying, both non‐metal dopants (P 23 and Si 24 ), as well as metal dopants (Li, 14,15 Mg, 12,16 and Ti 13 ) may decrease amorphization in B 4 C. Both experimental and theoretical studies have suggested that boron enrichment is helpful to mitigate amorphization 17–19 …”
Section: Introductionmentioning
confidence: 99%